JWST Reveals a Population of Ultrared, Flattened Galaxies at 2 ≲ z ≲ 6 Previously Missed by HST - Erica J. Nelson; Katherine A. Suess; Rachel Bezanson; Sedona H. Price; Pieter van Dokkum; Joel Leja; Bingjie Wang; Katherine E. Whitaker; Ivo Labbé; Laia Barrufet; Gabriel Brammer; Daniel J. Eisenstein; et al. (The Astrophysical Journal Letters, 2023)
With just a month of data, JWST is already transforming our view of the universe, revealing and resolving starlight in unprecedented populations of galaxies. Although “HST-dark” galaxies have previously been detected at long wavelengths, these observations generally suffer from a lack of spatial resolution, which limits our ability to characterize their sizes and morphologies. Here we report on a first view of starlight from a subset of the HST-dark population that is bright with JWST/NIRCam (4.4 μ m < 24.5 mag) and very faint or even invisible with HST (<1.6 μ m). In this Letter we focus on a dramatic and unanticipated population of physically extended galaxies (≳0.″25). These 12 galaxies have photometric redshifts 2 < z < 6, high stellar masses M _⋆ ≳ 10 ^10 M _⊙ , and significant dust-attenuated star formation. Surprisingly, the galaxies have elongated projected axis ratios at 4.4 μ m, suggesting that the population is disk dominated or prolate and we hence refer to them as ultrared flattened objects. Most of the galaxies appear red at all radii, suggesting significant dust attenuation throughout. With R _e (F444W) ∼ 1–2 kpc, the galaxies are similar in size to compact massive galaxies at z ∼ 2 and the cores of massive galaxies and S0s at z ∼ 0. The stellar masses, sizes, and morphologies of the sample suggest that some could be progenitors of lenticular or fast-rotating galaxies in the local universe. The existence of this population suggests that our previous censuses of the universe may have missed massive, dusty edge-on disks, in addition to dust-obscured starbursts.